TANGGUNG JAWAB GURU DALAM MEMBENTUK KARAKTER RELIGIUS PESERTA DIDIK DI TENGAH ARUS DIGITALISASI - Ayi Ali Hakim; Oktavia, Dita; Rahmasari, Anisa; Nur Khasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Digitalization presents a major challenge for character education, as moral and ethical values are often eroded by the negative influence of digital information. This study aims to analyze the responsibilities, roles, and strategies of teachers in shaping students’ religious character amid the tide of digitalization. The research method employed is a qualitative approach using literature review (library research). Data were collected through systematic searches of academic databases and analyzed using qualitative content analysis techniques through the stages of data reduction, thematic coding, and synthesis. The research findings indicate that teachers bear a crucial responsibility encompassing six strategic roles: instilling moral values, teaching the positive use of technology, fostering discipline, serving as digital role models, encouraging social collaboration, and teaching responsibility in the digital world. The strategies implemented include integrating Islamic values into digital learning, strengthening digital literacy based on Islamic values, and fostering synergistic collaboration with parents. Despite facing infrastructure, pedagogical, and socio-cultural challenges such as cyberbullying, effective solutions can be achieved through structured teacher training and the strengthening of a three-pillar school culture. The conclusion of this study emphasizes that the successful development of religious character in the digital age requires a comprehensive approach that integrates technological proficiency with the cultivation of noble moral values.